2006
DOI: 10.1364/ol.31.002756
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of basal cell carcinoma from normal dermal stroma by quantitative multiphoton imaging

Abstract: We performed multiphoton fluorescence (MF) and second-harmonic generation (SHG) imaging on human basal cell carcinoma samples. In the dermis, basal cell carcinomas can be identified by masses of autofluorescent cells with relatively large nuclei and marked peripheral palisading. In the normal dermis, SHG from dermal collagen contributes largely to the multiphoton signal. However, within the cancer stroma, SHG signals diminish and are replaced by autofluorescent signals, indicating that normal collagen structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
140
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(144 citation statements)
references
References 15 publications
4
140
0
Order By: Relevance
“…This combined technique has been widely used for imaging and characterizing human skin dermis. In particular, it has been used for monitoring collagen alteration in dermal disorders [50] or at the tumour-stroma interface [51][52][53], as well as to monitor skin aging by measuring the collagen/elastic fibres content [54][55][56].…”
Section: Introductionmentioning
confidence: 99%
“…This combined technique has been widely used for imaging and characterizing human skin dermis. In particular, it has been used for monitoring collagen alteration in dermal disorders [50] or at the tumour-stroma interface [51][52][53], as well as to monitor skin aging by measuring the collagen/elastic fibres content [54][55][56].…”
Section: Introductionmentioning
confidence: 99%
“…Collagen fibers produce a high SHG signal [18] and can be imaged inside skin dermis with SHG microscopy [4,18]. Recently, SHG was also used for investigating collagen-fiber orientation and their structural changes in fibrotic collagen [19], human dermis [20][21][22][23], keloid [24], cornea [25,26] and in the tumor microenvironment [27][28][29][30]. The combination of TPEF and SHG is particularly useful when imaging dermis tissue because the two main components of dermis (collagen and elastin) can be imaged with SHG and TPEF microscopy, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the recent reports have focused on visualizing collagen fibers in natural tissues including skin, tendon, blood vessels, and cornea (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). A smaller body of publications has described SHG imaging of acto-myosin complexes in muscle (13,14) as well as microtubule-based structures in live cells (13,15).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the connective tissue disorder Osteogenesis Imperfecta (OI) is characterized by abnormal collagen assembly and we have shown that SHG can reveal differences in the morphology not possible by other optical methods (16). Additionally, SHG has also shown early promise in imaging cancer since malignant tumors often have abnormal collagen assembly relative to normal tissue (9,17). …”
Section: Introductionmentioning
confidence: 99%